Pengaruh Pemberian Reward, Insentif dan Tunjangan Terhadap Kinerja Karyawan (Studi Kasus pada Karyawan JNE Cabang Utama Surabaya) - Siti Nurhasanah; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractWith the development of the world of industry and technology in human life, it can facilitate the movement of goods and information from one place to another. Along with the development of an increasingly broad market, companies need expedition services to expand their business reach. One of the most important factors in an organization is human resources, therefore the utilization of human resources is needed. In general, employees work because to meet their daily needs, so that employees will work harder if the work they do gets a reward or remuneration, one of the policies that companies can do to improve employee performance is to provide compensation. Performance is the result of the work done and has a strong relationship to the company's strategy. Performance is about how to get the job done and about what to do next. Reward is one of the factors that employees work in an organization. Reward is one of the motivators used by managers to create productivity and increase employee motivation at work. Incentives are a form of payment associated with employee performance, as well as distribution of income to employees. Incentives are compensation provided by the company, which is linked between pay and productivity. Allowance is a reward given by the company in order to provide peace and prosperity to employees to maintain and improve employee morale. Keyword : Performance, Reward, Incentives, and Allowance